Baseline dependency of nicotine's sensory gating actions: similarities and differences in low, medium and high P50 suppressors. (September 2013) - Knott, Verner; de la Salle, Sara; Smith, Dylan; Phillipe, Tristan; Dort, Heather; Choueiry, Joelle; Impey, Danielle
Reduced suppression of the P50 auditory event-related potential in schizophrenia patients relative to normal controls is indicative of a sensory gating deficit and is one of the most robust findings reported for functional brain abnormalities in this disorder. However, there is considerable gating variability in patients and controls and there is little understanding as to how inter-individual differences moderate gating responses to drugs and nicotinic agonists in particular, which have shown potential to reverse gating deficits. In this study the effects of acutely administered nicotine (gum, 6 mg) on sensory gating in a paired (S1 –S2 ) auditory stimulus paradigm were investigated in 57 healthy, non-smoking volunteers stratified as low ( n = 19), medium ( n = 19) and high ( n = 19) P50 suppressors on the basis of three separate baseline derived gating indices, P50 ratios, P50 difference scores, and gating difference waveforms. Relative to placebo, nicotine consistently improved gating in low suppressors as stratified with all three gating indices, exerted no effects in medium suppressors and reduced gating in high suppressors. Analysis of individual stimulus (S1, S2 ) amplitudes showed distinctly different mechanisms of action underlying nicotine effects in individuals with low and high baseline suppression. The results parallel similar findings of baseline-dependency in the gating effects of several antipsychotic drugs in healthy volunteers and support the use of group segmentation as a translational model in novel cognitive drug development for schizophrenia.